Challenges Of Post-Pandemic Government Management: Between Centralization And Regional Autonomy - Wildan Zaman (Pt. Anagata Sembagi Education, 2025)
The COVID-19 pandemic has exposed the tension between policy centralization and regional autonomy, changing the dynamics of governance in Indonesia. This study aims to analyze the challenges faced by regional governments in managing the pandemic, and its impact on central-regional relations in the context of post-pandemic governance. The findings show that policy centralization at the peak of the pandemic required close coordination between governments, but limited the flexibility of regional governments to adjust policies to local conditions. Despite the decline in regional revenues due to the pandemic, several regions showed high adaptability, such as the implementation of digital-based public service systems. In the post-pandemic era, there is an opportunity to reform central-regional relations, by prioritizing a hybrid model that provides more flexibility to regions while maintaining central oversight. This study suggests the need for broader fiscal decentralization, capacity building of regional institutions, and development of more efficient coordination systems to address future challenges. This study provides insights into more inclusive and responsive governance in the post-pandemic era.